2000
DOI: 10.1507/endocrj.47.443
|View full text |Cite
|
Sign up to set email alerts
|

Primary Aldosteronism due to Unilateral Adrenal Hyperplasia. Report of Two Cases and Review of the Literature.

Abstract: Abstract.Unilateral adrenal hyperplasia (UAH) is a rare, surgically correctable subset of primary aldosteronism(PA), which shows similar endocrine features to aldosterone-producing adenoma (APA). We report here two Japanese patients with UAH. Case 1 was a 62-year-old man with a four-year history of hypertension.Hypokalemia and suppressed plasma renin activity (PRA) with elevated plasma aldosterone concentration (PAC) were observed, while no adrenal nodules were identified by abdominal computed tomographic (CT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…There are several reports that bilateral uptake (22) or no uptake (23) or even incorrect side uptake might occur in patients with proven aldosterone producing adenoma (24). For cases of unilateral adrenal hyperplasia, adrenal scintigraphy with or without dexamethasone treatment has been used in 8 cases with varying results: four had a bilateral uptake, 2 had the correct uptake, and 1 had early uptake on the correct side on day 3 followed by bilateral uptake on day 5 ( 6,9,11,13,14,18). In these cases, dexamethasone suppression did not improve the determination of the affected site.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports that bilateral uptake (22) or no uptake (23) or even incorrect side uptake might occur in patients with proven aldosterone producing adenoma (24). For cases of unilateral adrenal hyperplasia, adrenal scintigraphy with or without dexamethasone treatment has been used in 8 cases with varying results: four had a bilateral uptake, 2 had the correct uptake, and 1 had early uptake on the correct side on day 3 followed by bilateral uptake on day 5 ( 6,9,11,13,14,18). In these cases, dexamethasone suppression did not improve the determination of the affected site.…”
Section: Discussionmentioning
confidence: 99%
“…The stasis of contrast medium may occur on the delayed phase in a tumour mainly composed of clear cells in comparison with a compact cell‐rich tumour. Although the same logic can be applied to AA, previous reports have shown that lipid‐rich AAs do not demonstrate washout patterns different from those of lipid‐poor AAs . However, the authors divided adenomas into lipid‐rich and lipid‐poor groups using non‐enhanced CT attenuation values and did not perform histological analyses of each AA.…”
Section: Discussionmentioning
confidence: 99%
“…These two diseases can be differentiated from pheochromocytoma, adrenal metastasis and adrenal cancer, which reportedly show low washout rates . AH is composed of clear cells and compact cells and closely resembles AA in histology, although AH is differentiated from AA using several findings such as bilaterality, not encapsulated margin and a transition into the surrounding adrenal cortex as a whole . Not only AA but also AH show variable washout rates, but the difference in washout rates within the same disease has not been fully investigated, and the details are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, differentiating between APA and IHA can be extremely challenging for three reasons: 1) there are rare cases of MUAN, or unilateral autonomous hyperplasia, that can be cured by adrenalectomy [13]; 2) at histopathology the border between a microscopic adenoma and a unilateral hyperplasia or MUAN is undefined; and 3) bilateral APA and APA in the context of BAH can exist [14,15].…”
Section: Clinical Forms Of Primary Aldosteronismmentioning
confidence: 99%